Potential tumor markers of renal cell carcinoma: α‐Enolase for postoperative follow up, and galectin‐1 and galectin‐3 for primary detection. (1st November 2012) - Kaneko, Naoki; Gotoh, Akinobu; Okamura, Noboru; Matsuo, Ei‐ichi; Terao, Shuji; Watanabe, Makoto; Yamada, Yuji; Hamami, Gaku; Nakamura, Tsutomu; Ikekita, Masahiko; Okumura, Katsuhiko; Nishimura, Osamu
Abstract: The diagnosis of renal cell carcinoma is currently based on imaging techniques, mainly because there is no blood marker available for its detection. Thus, there is still the need for the development of novel tumor markers. We examined plasma levels of eight proteins in 15 renal cell carcinoma patients before and after surgery, and in 51 healthy controls using enzyme‐linked immunosorbent assay. Plasma levels of α‐enolase, calnexin, galectin‐1, galectin‐3 and lectin mannose‐binding 2 were significantly higher in renal cell carcinoma patients than in controls ( P < 0.05). Among these proteins, the sensitivities for galectin‐1 and galectin‐3 were higher than those for calnexin and lectin mannose‐binding 2 in the specificity range from 80% to 100%. A combined use of galectin‐1 and galectin‐3 showed 98% specificity and 47% sensitivity. In addition, the assays showed that plasma α‐enolase levels decreased significantly 4 weeks after nephrectomy ( P = 0.0034), and this tendency continued until 12 weeks after nephrectomy ( P = 0.0156). These findings suggest that α‐enolase could be used in the postoperative follow up of renal cell carcinoma patients, whereas the combined use of galectin‐1 and galectin‐3 might represent a useful tool for primary detection.